Applied physiology in perioperative medicine: a concept for the future - Molnar, Zsolt; Benes, Jan; Saugel, Bernd (Journal of Emergency and Critical Care Medicine, 2020)
Surgery has become safer and safer over the last decades on the one hand as a result of highly sophisticated non-invasive approaches that aim to replace operations with excessive tissue trauma and on the other hand due to the developments in anesthesiology and intensive therapy. The latter has been mentioned more and more frequently in the context of perioperative medicine often referred to as an entity on its own. This means that pre-, intra-, and postoperative care should not be considered as independent components managed by different teams but rather dealt with as one process and managed by using a holistic approach.